Effect of Nitrogen Ion Implantation Energy on the Mechanical and Chemical Properties of AISI M50 Steel. (12th October 2021) - Xie, Xiangyu; Chen, Chao; Luo, Jun; Xu, Jin
Abstract : Nitrogen ion implantation has shown its role in enhancing steel surface properties. In this work, AISI M50 steel was implanted with nitrogen ions by using the metal vapor vacuum arc technique with a dose of 2 × 10 17  cm −2, and corresponding implanted energies were at 60 keV, 80 keV, and 100 keV, respectively. The distribution of implanted nitrogen ions was calculated, and the samples were tribologically tested and examined. As shown by the results, the microhardness in implanted samples was 1.17 times greater relative to that of the unimplanted sample. The implantation of the nitrogen ion leads to a change in the friction coefficient of the AISI M50 steel. Adhesive wear mechanism occurs in the unimplanted sample, and adhesion resistance tends to increase when nitrogen-implanted energy increases. The formation of oxides α -Fe2 O3 and Fe3 O4 further enhanced the tribological properties for implanted samples.